A nine-month temptation - Rock, Joanne (Brooklyn nights series., 2021)
One night rocked their world. Now can they tame their passion for their baby's sake? Ever since their mind-blowing encounter months ago, fashion CEO Roman Zayn hasn't stopped hungering for Sable Cordero. But as a rising star in his brother's design studio, the intoxicating celebrity stylist is strictly off-limits. Even when Roman discovers Sable is pregnant and steps in to offer support, further intimacy between them feels forbidden. But resistance to an attraction like theirs just may prove futile...